Compensation for Moral Damage within the Scope of Contractual Liability under the Jordanian Civil Code: A Comparative Study - Al Dajeh, Bakhit; Rayyan, Ihab (Journal of Legal Sciences, 2025)
Compensation for moral (non-pecuniary) damage remains a vital issue in civil law, reflecting the legal system’s commitment to safeguarding human dignity and emotional well-being beyond material interests. Such damage typically arises from psychological harm, defamation, or negligence that inflicts emotional suffering difficult to quantify yet deeply affecting the injured party. While this form of harm is traditionally addressed within tortious liability, its recognition under contractual liability remains controversial and legally uncertain. This study explores the extent to which compensation for moral damage can be granted within contractual relations under the Jordanian Civil Code. It identifies a legislative gap and analyzes judicial and comparative perspectives to determine whether existing legal provisions implicitly allow such compensation. Adopting descriptive, analytical, and comparative methodologies, the research examines relevant statutory texts, doctrinal opinions, and judicial reasoning in Jordan and other civil law systems. The findings reveal that Jordanian law does not explicitly regulate moral damage within contractual liability, leaving interpretation to courts. The study recommends formal recognition of such compensation, given its impact on the contracting party’s dignity and emotional state, and argues that doing so would strengthen justice, contractual confidence, and alignment with contemporary comparative legal developments.